TINJAUAN YURIDIS SURAT KETERANGAN (COVERNOTE) DALAM PEMBERIAN KREDIT KONSUMEN DENGAN JAMINAN SERTIFIKAT TANAH YANG DIBEBANKAN HAK TANGGUNGAN PADA PT. BPR TUNAS MITRA MANDIRI PEKANBARU - Tengku Indra Adiputra; Maryati Bachtiar; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Society generally still believe that Professional Notary And PPAT have in common, but both Profession Among these are differences, case singer or between lie caused Notary PPAT usually occupied by same thing. Notary officer sales manager that is authorized to review make authentic act and have more authority as hearts revoked Article 1 of Law No. 2 of 2014 ABOUT Amendment Act No. 30 of 2004 ABOUT Notary. And in deed between letter made by Notaries, Notary usually make certificate also, only prayer is a form of letter "Covernote".Purpose o f research singer, for knowing consideration PT. BPR Mitra Mandiri Tunas Pekanbaru with hearts give credit collateral land titles the basic differences imposed security rights basis Covernote certificate or, for knowing the position of the certificate or Covernote hearts security law on with collateral lending practices certificate soil that charged security rights.Covernote role is to help the binding process credit review what where parties BPR TMM increased its guarantee is the right of dependents. The Covernote often used as evidence assurance / grip temporary share hearts Bank credit disbursement process, then hearts certificate issuance security rights Covernote become part of the process of forming prayer events that treaty law credit loan agreement and collateral agreement / binding encumbrance. The binding process warranty certificate ground charged encumbrance until with tied with Perfect is expected to take approximately three (3) months from the date of power attorney Installing security rights (SKMHT) Published, so it can be ascertained if process of loan disbursement done taxable income the completion of the process Then binding security rights will cause operational disruption Services Bank, particularly Subscribe with lending.Supposedly There a provision as a legal umbrella Notary The issuing Covernote and parties-parties the interest thing using services Notary especially subscribe with Covernote purpose to minimize the disadvantage good from parties Notary or from parties users Notary services (Bank) and suggested shown to the parties the Bank to always do evaluation performance with Notary that has collaborated Bank, with attention to the Notary success rate fg hearts do binding of security rights.Keywords: Covernote Notary - Security Rights